2012
DOI: 10.1258/ebm.2011.011220
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic pump manipulation mobilizes inflammatory mediators into lymphatic circulation

Abstract: Lymph stasis can result in edema and the accumulation of particulate matter, exudates, toxins and bacteria in tissue interstitial fluid, leading to inflammation, impaired immune cell trafficking, tissue hypoxia, tissue fibrosis and a variety of diseases. Previously, we demonstrated that osteopathic lymphatic pump techniques (LPTs) significantly increased thoracic and intestinal duct lymph flow. The purpose of this study was to determine if LPT would mobilize inflammatory mediators into the lymphatic circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
(37 reference statements)
3
31
0
1
Order By: Relevance
“…12) The accumulation of toxins, exudate, the fine particles contained in lymph, and bacteria in tissue brings about a variety of changes, including inflammation, a low oxygen environment, and fibrosis. 13,14) In this study, we demonstrated that during lymphostasis, lipid molecules accumulate in the tissue surrounding veins. Based on these findings, we will attempt to discuss the mechanism responsible for lipid molecule accumulation and metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 56%
“…12) The accumulation of toxins, exudate, the fine particles contained in lymph, and bacteria in tissue brings about a variety of changes, including inflammation, a low oxygen environment, and fibrosis. 13,14) In this study, we demonstrated that during lymphostasis, lipid molecules accumulate in the tissue surrounding veins. Based on these findings, we will attempt to discuss the mechanism responsible for lipid molecule accumulation and metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 56%
“…5,12 Previously, we demonstrated that a single application of LPT increased lymph flow and leukocyte flux in both rats and dogs, and mobilized inflammatory mediators into lymph circulation. [13][14][15][16][17][18][19] These findings support the use of LPT to treat edema and to enhance immune function. Importantly, the effects of LPT on the lymphatic system were transient, suggesting this LPT-sensitive lymph reservoir is limited.…”
Section: Introductionmentioning
confidence: 62%
“…Importantly, the effects of LPT on the lymphatic system were transient, suggesting this LPT-sensitive lymph reservoir is limited. [13][14][15][16][17][18][19] The purpose of this study was to determine if a second application of LPT could also enhance lymph flow, the number of leukocytes, and the concentration of inflammatory mediators in thoracic duct lymph. Our results demonstrate that LPT can be repeatedly applied to enhance lymph flow, leukocyte numbers, and the flux of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphatic pump techniques have been shown to increase cytokines and chemokines in thoracic and intestinal lymph vessels 35 , while mechanical pressure to certain body regions distant from the location of lymph formation enhances flow into lymphatic systems 36 . In addition, it has been shown that lymphatic OMT augments leukocyte mobilization and flow in dogs and rats, primarily from gut-associated lymphoid tissue 37,38,39,40,41 .…”
Section: Representative Resultsmentioning
confidence: 99%